Study of fish fillet defrosting in the ultrasonic field - A. V. Kozachenko; V. A. Demchenko (Новые технологии)
The article presents the studies of the influence of ultrasonic treatment on the speed and quality of fish fillet defrosting - cod and tilapia. The results of physical and chemical studies of ultrasonically treated defrosted fish are presented. A laboratory installation for carrying out experimental work has been described. A method for fish fillet defrosting using an ultrasonic generator is proposed. It’s been established that the use of ultrasonic treatment significantly shortens the term of the defrosting process and does not affect the organoleptic parameters of the quality of fish fillet defrosting. Optimum mode of equipment operation is selected.